Design And Development Of Path Planning Techniques For A Tennis Ball Retriever Robot - Chee, Kiang Lam; Ali, Mohanad Faeq; Lam, C. K.; K.V. Ch’ng; Sundaraj, Kenneth; Tan, Wen Hong (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
During a tennis solo training,players usually train using an automatic ball launcher machine.After some time, they are required to collect all the balls scattered all around the court themselves to refill the launcher machine. This is a physically challenging procedure, which is generally loathed by keen tennis players and may cause unwelcome injuries. This study aims to design of an autonomous tennis ball retriever that will discard all the unnecessary energy and time wasting in traditional ball picking up method. This robot will sweep all the balls using a suitable path planning technique. After this, a few path planning methods such as Coverage Path Planning (CPP) U-Turn,CPP ISS,and Probabilistic Roadmap Method (PRM) were integrated into the tennis ball retriever robot for comparison. After comparison between all the experiment done,CPP U-Turn is proven the best path planning method among the three tested algorithms to be integrated into a tennis ball retriever robot.